SHOVEL PLATE PARAMETERS OPTIMIZATION BASED ON THE SUBSTEP MULTI-OBJECTIVE OPTIMIZATION METHOD - LI Qiang; MAO Jun; ZHANG MingYu; XIE Miao (Jixie qiangdu, 2017)
Aiming at the vulnerability poor quality and need prior knowledge of traditional mathematical programming theory on multi-objective optimization in practical engineering optimization problem. Put forward an improved particle swarm optimization conjugated the criterion with minimum Euclidean distance to a base value and then combined with grey decision to make multiobjective optimization. Applied the above multi-objective optimization method on roadheader shovel plate parameters and have done some simulation on shovel plate grubbing coal rock,has obtained a good optimization effect. By doing so,it verifies the feasibility of this method and provides convenience and reference to deal with multi-objective optimization problems in engineering practice.